Pelatihan Pengembangan Paguyuban UMKM Bertransformasi Menjadi Digitalisasi Koperasi Produsen di Kota Surabaya - Sulistyo Budi Utomo; Heru Suprihhadi; Mega Arisia Dewi; In’am Widiarma (Jurnal Pengabdian Masyarakat (abdira), 2022)
The purpose of this service is that there are pro-populist funding alternatives that empower the people's economy and MSMEs in particular, so it is an opportunity for cooperatives to strengthen the basis for the commonality of these goals with the welfare of their members. The role of academics and practitioners is very much needed in providing assistance to MSMEs considering that statistical data shows that the number of MSME actors is increasing and it is expected to increase their capacity and expertise in all fields. The problems faced by MSMEs are not only the lack of assistance, but the main obstacle is the availability of capital and the difficulty of accessing financing from financial institutions. The results of the service are getting easy access to funding by strengthening the function of modern cooperatives and supporting MSMEs to transform following the digital era, namely using digitalization services to be in line with the Industrial Revolution 4.0.